“XÔ FOME”, AGAINST THE HUNGER AND WASTE (CIPEEX, 2024)
Imagine a world where helping others becomes just a click away, where each donation is a step towards a new future, with less waste and hunger. This is the “Xô Fome” project, where the future begins. This project aims to combat hunger and food waste with a social media of community aid, which promotes empathy, donation and sustainable production. It consists of a donation app, where applicants can make their requests for donors. Through a posting system, people can view applicants' needs and indicate items they want to donate or what is needed. This way, the donor will be able to see the requests for help and decide to donate to the right people. Aiming for the correct use of these resources, will be implemented a token, as a form of internal capital transaction, which can be purchased with money and exchanged for products in affiliated stores of the app, they will carry out promotions on products, focusing on products close to their expiration date so that they can be fully utilized. These promotions may occur within the app or during the exchange process at establishments. Then, within the system, there will be three main actors: the user who receives, the user who donates and the establishment with promotions and affiliation. When developing this environment, the navigation area of the donor and the applicant will be the same, although they take different paths, the user will be able to both donate and receive a donation if they open a publication. Enterprises will have a different approach with their own interface so they can manage all their products and promotions. They will also be able to visualize their engagement and that of their products. With membership, companies will have a social tool that helps them avoid losses and the community in which they operate, in addition to likely tax exemption. After discussing how it will work, the intended audience are, for the most part, people who have had a sudden financial change, some examples like: unemployed or self-employed people who have health problems that make it impossible to practice their profession. According to the UN, today around 17% of all food produced is discarded in a reality where 735 million people are hungry in the world, imagine now the impact that would be achieved by reducing the percentage of loss. In addition to helping establishments, this could provide low-cost products to users who are in difficult situations. Within this proposal, the expectation is to promote a solidarity network that is a tool for people in need and a bridge for people and businesses that want to help fight against these current situations. In conclusion, the “Xô Fome” project seeks to create a network of communities that fight against hunger and waste. With an innovative app and the integration of donors, beneficiaries and establishments, it offers a practical and sustainable solution to a global problem.
Keywords: Hunger, Donation; Responsible Consumption; Token.